Asuhan Kebidanan Komprehensif Pada Ny. F Umur 26 Tahun G2p0a1 Presentasi Bokong Dengan Persalinan Sectio Caesarea Di Wilayah Kerja Puskesmas Bumiayu Kabupaten Brebes Tahun 2023 - Tika Arniza Meidina; Endang Susilowati; Nurhidayah Nurhidayah (Jurnal Anestesi, 2024)
Breech presentation is a pregnancy with an elongated position og the baby where the fetal head is in the fundus and the buttocks are the lowest part of the fetus and most fetuses can carry out a spontaneous version of cephalic presentation at term. Pregnancies with breech presentation with a total of 229 people (Indonesia health profile, 2020). Based in the results of pregnancy, childbirth, newborn, postpartum and family planning care, there was only a problem during the first pregnancy visit at 34 weeks of gestation, namely breech presentation. The researcher implemented comprehensive midwifery care using Varney dan SOAP documentation. This research aims to enable pregnant women to know and understand the location, prevention and treatment. This research uses a qualititave descriptive method with a case study approach. Data collection uses interview methods, observation, physical examination, supporting examinations, medical records, KIA books and other literature. Conclusions in the research can be concluded that health research can broaden the knowledge of pregnant women and can also understand the importance of the dangers of breech presentation delivery.